MINDFULNESS AND MIND-WANDERING IN PRAYER: A MIXED METHODS STUDY OF THE ROLE OF SPIRITUALITY AND RELIGIOSITY IN ISLAMIC PREACHERS - Syamila, Millati; Mansoer, Winarini Wilman D. (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Prayer is a subjective experience that requires solemnity, by seeking a state of mindfulness and minimizing the state of mind wandering so that the prayer is done optimally. This study aims to explore the role of spirituality and religiosity to increase mindfulness and minimize mind-wandering in prayer activities, in Islamic preachers. Analysis was conducted through mixed method explanatory sequential analysis, using quantitative data with Multiple linear regression and qualitative data with Thematic analysis. Qualitative data (n = 3) was used to explore the experience of the meaning of mindfulness and mind-wandering conditions during prayer which was tested using quantitative data (n = 66). The quantitative analysis showed that mindfulness was negatively correlated with mind-wandering in prayer and that religious salience predicted mindfulness. Meanwhile, the experience of mind-wandering in prayer can be explained more qualitatively. There are 3 major themes regarding the experience of mindfulness and mind-wandering as well as the role of spirituality and religiosity in Islamic preachers, namely 1) solemn conditions, consisting of the involvement of a) mental representation, b) mental dialogue, c) expectation, d) control of consciousness, e) appreciation of life experience, and f) feeling comfortable and full of enjoyment, 2) mind-wandering distraction, which consists of the presence of a) worldly ambitions and b) perceptual distraction, and 3) spiritual atmosphere conditioning, consisting of a) preparation of prayer pillars, b) self-preparation, and c) asking for protection.